1997
DOI: 10.1177/0310057x9702500605
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Short Intravenous Infusions of Thiopentone on Myocardial Function, Blood Flow and Oxygen Consumption in Sheep

Abstract: The cardiovascular effects of slow (over two minutes) intravenous infusions of thiopentone 750 mg in conscious instrumented sheep breathing 100% oxygen were examined for 30 minutes following the start of the infusion. The maximum rate of rise of left ventricular pressure (an index of myocardial contractility) decreased significantly from 1 to 10 minutes, to a minimum of 45% of baseline. Heart rate increased by up to 33% above baseline from 0.5 min onwards. Both mean arterial pressure and cardiac output were de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 23 publications
(40 reference statements)
1
5
0
Order By: Relevance
“…Although rac ‐thiopentone has a long history of successful clinical use it also has some recognized drawbacks. It causes myocardial and respiratory depression, and its repeated use leads to prolonged time to awakening (Crankshaw, 1987; Hirshman et al ., 1975; Huang et al ., 1997; Upton et al ., 1997). We believe that there is now sufficient evidence to suggest that substitution of enantiopure R‐thiopentone for the clinically used rac ‐thiopentone may have merit.…”
Section: Discussionsupporting
confidence: 94%
“…Although rac ‐thiopentone has a long history of successful clinical use it also has some recognized drawbacks. It causes myocardial and respiratory depression, and its repeated use leads to prolonged time to awakening (Crankshaw, 1987; Hirshman et al ., 1975; Huang et al ., 1997; Upton et al ., 1997). We believe that there is now sufficient evidence to suggest that substitution of enantiopure R‐thiopentone for the clinically used rac ‐thiopentone may have merit.…”
Section: Discussionsupporting
confidence: 94%
“…18 Previous work has shown that thiopental 750 mg over 2 min transiently reduced cardiac output for approximately 6 min to a minimum of 75% of baseline. 19 Given the fundamental role of cardiac output in this type of model, 11 it was felt the model should account for this observation. Hybrid effect compartment analysis with linear, Emax and sigmoid Emax dynamic models were used to compare the time course of changes in cardiac output with the time course of arterial concentrations of thiopental.…”
Section: Thiopental Effects On Cardiac Outputmentioning
confidence: 99%
“…This finding agrees with the work done by Pundits (2008) who discovered the occurrence of respiratory depression and apnoea after thiopental administration. Similarly, earlier studies have shown that thiopentone injection caused pulmonary depression (Gaudy et al, 1983;Huang et al, 1997;Gargiulo et al, 2012).…”
Section: Discussionmentioning
confidence: 62%